Design and Implementation of a Visible Light-Based Pest Stinger System - Wahab, Faisal; Maria Diamond, Ivana; Fredy Naa, Christian (Emitor: Jurnal Teknik Elektro, 2025)
The agricultural yield in Indonesia has been declining, partly due to shrinking farmland. To address this issue, urban farming has been developed as a solution. However, in urban farming, there is a problem where the leaves of vegetables are infested by insect pests, causing damage to the leaves. Therefore, pest control is necessary in the farming area. One alternative for controlling insect pests is by applying high-voltage electricity to the pests, which will kill them by electric shock with a voltage of around ±1 kV. A "Joule thief" circuit is designed to increase the input voltage below 9 volts to an output voltage of ±1 kV. There are also supporting components, such as a lamp that emits ultraviolet light, to attract the pests. A monitoring system is also designed to allow operators to know the environmental conditions of the vegetable farm, such as soil moisture, air humidity, light intensity, and notifications if the insect carcass container is full. During testing of the trap, there was an issue with the internet connection, so a backup circuit was made to keep the device running according to the schedule without an internet connection. This pest trap was tested for 5 days, and the number of trapped pests increased each day, leading to the conclusion that this device effectively traps pests.